The Digital Village Initiative and Construction of Social Identity in Rural Communities - Alfian, Rahman Latif; Warto, Warto; Fauziah, Nike Mutiara; Widyaningsih, Rindha (Universitas Andalas, 2025)
In the era of technological and information modernization, the need for information is one of the basic needs for human life. It makes various community groups develop ways of life to meet these needs. One of them was carried out by the people of Melung Village, who independently built an internet network in their village to obtain access to information from outside Melung Village. The difficult location and being in the mountains make this business known to many, so Melung Village is nicknamed the Internet Village or Digital Village. In its development, this embedded predicate, or nickname affects how people recognize themselves and represent their identity. This research wants to explore more deeply how the dynamics and formation of sociocultural identities for the community are located. This study uses ethnographic methods to obtain field data. Ethnography was chosen to obtain data from the perspective of cultural stakeholders, in this case, the people of Melung village. The results of this study show that the people of Melung Village do not deliberately embed the identity of the digital village but rather introduce the public to Melung Village, a remote village with good internet access. In its development, this identity is interpreted by the community not only as the identity of the village but also as the identity of the people of Melung Village.